Critical care by emergency physicians in American and English hospitals. Issue 3 (September 1993) - Graff, L G; Clark, S; Radford, M J
Abstract : The object of this study was to compare emergency physician critical care services in an American (A) and an English (E) Emergency Department (ED). A prospective case comparison trial was used. The study was carried out at two university affiliated community hospitals, one in the U.S.A and one in England. Subjects were consecutive patients triaged as requiring critical care services and subsequently admitted to the hospital ward (A, n = 17; E, n = 18) or the intensive/critical care unit ([ICU] A, n = 14; E, n = 24). The study time period was randomly selected 8-h shifts occurring over a 4-week period. All patients were treated by standard guidelines for critical care services at the study hospital emergency department. For all study patients mean length of stay was significantly longer for the American (233 min, 95% CI 201, 264) than the English ED (24 min, 95% CI 23, 25). American emergency physicians spent less total time providing physician services (19.2 min, 95% CI 16.8, 21.6) vs. (23 min, 95% CI 21.6, 24.4) than English emergency physicians. American emergency physicians spent less time with the patient than English emergency physicians: 12.4 min (95% CI 10.3, 14.5) vs. 17 min (95% CI 15.8, 18.2). American emergency physicians spent more time on the telephone 1.8 min (95% CI 1.4, 2.2) vs. 1.2 min (95% CI 1.1, 1.3), and in patient care discussions/order giving 1.8 min (95% CI 1.4, 2.2) vs. 1.1 min (95% CI .8, 1.4), There was no significant difference in time charting (3.2 min, 95% CI 2.8, 3.6 vs. 3.5 min, 95% CI 3.2, 3.8). Results did not vary significantly whether analysed subgroups or the whole study group. American emergency physicians provided 81% of their service during the first hour. There were delays at the American hospital until the physician saw the patient: 4.9 min (95% CI 2.5, 7.3) for patients admitted to the ICU/CVU (Cardiovascular Unit), and 9.2 min (95% CI 4.6, 13.8) for patients admitted to the ward. At the American hospital, ICU/CVU physicians provided additional physician services in the emergency department whether the patient was admitted to the ward (6.7 min, 95% CI 5.5, 7.9) or the ICU/CVU (12.1 min, 95% CI 8.8, 15.9). For patients admitted to the ICU/CVU 47% of the length of stay was spent waiting for a bed to become available after the decision to admit had been made. Emergency physicians at E provided critical care services almost continuously during a short stay in the ED. Emergency physicians at A provided services intermittently with most services during an initial period of stabilization. Further study is necessary to identify what factors contribute to these different approaches to critical care in the ED.